2016
DOI: 10.1111/pbi.12644
|View full text |Cite
|
Sign up to set email alerts
|

Double overexpression of DREB and PIF transcription factors improves drought stress tolerance and cell elongation in transgenic plants

Abstract: SummaryAlthough a variety of transgenic plants that are tolerant to drought stress have been generated, many of these plants show growth retardation. To improve drought tolerance and plant growth, we applied a gene‐stacking approach using two transcription factor genes: DEHYDRATION‐RESPONSIVE ELEMENT‐BINDING 1A (DREB1A) and rice PHYTOCHROME‐INTERACTING FACTOR‐LIKE 1 (OsPIL1). The overexpression of DREB1A has been reported to improve drought stress tolerance in various crops, although it also causes a severe dw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(98 citation statements)
references
References 61 publications
4
94
0
Order By: Relevance
“…DREB genes from several species have been reported to be functionally involved in the regulation of plant responses to drought. These include Arabidopsis DREB1A and DREB2A (Kudo et al ., ; Yamaguchi‐Shinozaki and Shinozaki, ), soya bean GmDREB2 (Chen et al ., ) and GmERF3 (Zhang et al ., ), tomato JERF1 (Zhang et al ., ) and SIERF5 (Pan et al ., ) and apple MsDREB6.2 (Liao et al ., ), among others.…”
Section: Discussionmentioning
confidence: 99%
“…DREB genes from several species have been reported to be functionally involved in the regulation of plant responses to drought. These include Arabidopsis DREB1A and DREB2A (Kudo et al ., ; Yamaguchi‐Shinozaki and Shinozaki, ), soya bean GmDREB2 (Chen et al ., ) and GmERF3 (Zhang et al ., ), tomato JERF1 (Zhang et al ., ) and SIERF5 (Pan et al ., ) and apple MsDREB6.2 (Liao et al ., ), among others.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, gene-stacking approaches have proven fruitful in overcoming growth inhibition using positive regulators of drought responses such as DEHYDRATION-RESPONSIVE ELEMENT BINDING PROTEIN1A (DREB1A). Overexpression of DREB1A led to increased drought tolerance and growth inhibition, but the growth limitation could be overcome by simultaneous overexpression of DREB1A together with the rice homolog of PIF4 (OsPIL1) in Arabidopsis (Kudo et al, 2016). Along these lines, an elegant study demonstrated that overexpressing the BR receptor gene BRL3 increased plant survival during drought without the growth penalty observed in BR mutants such as the loss-of-function mutant bri1 (Fàbregas et al, 2018).…”
Section: Tissue-specific Modulation Of the Br Pathway Allows For Incrmentioning
confidence: 99%
“…Although the regulatory functions of the PIFs have been widely explored in light responses, seed germination and hormone regulation, the roles of PIFs in the drought stress response remain elusive (Leivar and Quail, 2011;Oh et al, 2009). The rice PIF-like protein OsPIL1 is down-regulated under drought stress conditions (Todaka et al, 2012), and overexpression of both DREB1A and OsPIL1 enhances drought tolerance in Arabidopsis (Kudo et al, 2016), while ZmPIF3 regulates plant responses to drought stresses (Gao et al, 2015). Thus, PIFs likely play complicated roles under drought stress.…”
Section: Introductionmentioning
confidence: 99%